A 76.8 MHz temperature compensated MEMS reference oscillator for wireless handsets. Issue 6 (June 2015) - Kourani, Ali; Hegazi, Emad; Ismail, Yehea
Abstract This paper reports on the design of a low phase noise 76.8 MHz AlN-on-silicon reference oscillator using <alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgpwn2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />SiO2</alternatives> as temperature compensation material. The paper presents profound theoretical optimization of all the important parameters for AlN-on-silicon width extensional mode resonators, filling into the knowledge gap targeting the tens of megahertz frequency range for this type of resonators. Low loading CMOS cross coupled series resonance oscillator is used to reach the-state-of-the-art LTE phase noise specifications. Phase noise of −123 dBc/Hz at 1 kHz, and −162 dBc/Hz at 1 MHz offset is achieved. The oscillator׳s integrated root mean square RMS jitter is 106 fs (10 kHz to 20 MHz), consuming 850 μA, with startup time of 250 μs, and a figure-of-merit FOM of 216 dB. This work offers a platform for high performance MEMS reference oscillators; where, it shows the applicability of replacing bulky quartz with MEMS resonators in cellular platforms.